Is Quality of Life of Lupus Better than Systemic Sclerosis? - Laniyati Hamijoyo; Nadia Gita Ghassani; Bernard Santoso Suryajaya; Ignatius Irawan Hidayat; Valentine Natasya Moenadi; Sasfia Candrianita; Sumartini Dewi (Indonesian Rheumatology Association, 2019)
Background. Patients with systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), have to cope with lifelong disease manifestation and impaired physical function. Limited physical activities along the disease will affect their quality of life (QoL). The QoL is recognized as an important factor of treatment strategy. This study aims to compare the quality of life of patient with SLE and SSc. Methods. This study was a cross-sectional study and conducted in rheumatology outpatient clinic of Hasan Sadikin Hospital Bandung, Indonesia from January 2015 until March 2017. The respondents were patients diagnosed as SLE and SSc who regularly visit rheumatology outpatient clinic. Respondents were asked to complete the Short Form-36 (SF-36). Baseline characteristics, including age, gender, and duration of disease, were collected during the visit. The Mann-Whitney U test was used to analyze the comparison. Results. There were 242 patients who completed the SF-36 questionnaires, consisted of 193 SLE patients and 49 SSc patients. SLE patients were slightly younger and had a longer duration of disease compared to SSc. The SF-36 Physical Component Summary (PCS) score was significantly higher on SLE patients (40.6 vs 40.4, p = 0.0001), but the mean of Mental Component Summary (MCS) score was similar among both diseases. Conclusion. Physical functioning aspect on quality of life is better in SLE patients compared to SSc patients. However, mental aspect for both diseases are relatively similar.